Kajian Olahraga Parkour Pada Konsep Kinematika Dasar Sebagai Inovasi Sumber Belajar Fisika - Rayhan Ardiansyah; Irnin Agustina Dwi Astuti; Luluk Setyowati (Schrodinger Jurnal Ilmiah Mahasiswa Pendidikan Fisika, 2022)
Students often have difficulty in understanding material about motion kinematics, the cause of which is the lack of material samples, or examples of questions and practice questions involving physical phenomena in everyday life. The purpose of this study is to provide information and learning resources with motion kinematics material using parkour sports, as studies are made to provide insights, and this information can provide students with an understanding of motion kinematics, which is often applied in everyday life.The method used is a qualitative research method, namely literature review. Motion kinematics (regular straight motion, regularly changing straight motion, parabolic motion, free fall motion, and circular motion) will be studied from parkour informatively so that students can know what kinematics theory is covered. So that the results of this study show that Prakour sports can be used as a source of learning physics on the concept of kinematics.